Origanum dictamnus Essential Oil in Vapour or Aqueous Solution Application for Pepper Fruit Preservation against Botrytis cinerea - Tzortzakis, Nikos G. (My University, 2024)
The use of synthetic sanitizers for fresh commodities preservation is of concern, with eco-friendly alternatives, including essential oils (EOs), attracting research and industry interest. Dittany (Origanum dictamnus—DIT) oil was applied, either through vapour or dipping, on pepper fruit or in vitro against Botrytis cinerea, and compared to untreated (control) or chlorine (CHL)-treated fruits stored at 11 °C. Direct DIT vapours (up to 6 d) suppressed lesion growth, spore germination, and spore production compared to the untreated fruits. The antimicrobial properties of EOs were evidenced in pre-exposed-to-DIT oil vapours (residual effect), resulting in fruit lesion suppression. However, DIT-pretreated fruits had the same spore production and spore germination as the control and CHL applications. In in vitro tests, DIT vapours decreased colony growth and spore production when fungi were grown on Potato Dextrose Agar (PDA) or PDA pre-exposed to DIT following B. cinerea inoculation. This evidenced that the disease suppression after DIT vapour application primarily affected the interaction of the fruit–pathogen and/or residual responses on fruit tissue and/or PDA media. Fungal biomass in Potato Dextrose Broth (PDB) was evaluated after DIT and CHL applications (10–50–100–500–5000 μL L−1) and decreased with the DIT oil. Additionally, DIT or CHL sanitary dipping on pepper was ineffective against B. cinerea compared to vapour application. Therefore, DIT vapours revealed antimicrobial properties and could be an alternative postharvest sanitiser. DIT oil application should also be evaluated at semi-commercial scale for further optimizations, prior to commercialisation.
Keywords: sanitizers; Capsicum annuum; essential oil; fruit decay; grey mould